2022
DOI: 10.1101/2022.03.15.484018
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamic single-cell RNA sequencing reveals BCG vaccination curtails SARS-CoV-2 induced disease severity and lung inflammation

Abstract: COVID-19 continues to exact a toll on human health despite the availability of several vaccines. Bacillus Calmette Guerin (BCG) has been shown to confer heterologous immune protection against viral infections including COVID-19 and has been proposed as vaccine against SARS-CoV-2 (SCV2). Here we tested intravenous BCG vaccination against COVID-19 using the golden Syrian hamster model together with immune profiling and single cell RNA sequencing (scRNAseq). We observed that BCG reduced both lung SCV2 viral load … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 77 publications
0
8
0
Order By: Relevance
“…Single-cell transcriptome profiling demonstrated higher recruitment of plasma cells, Th1, Th17, regulatory T cells (Treg), cytotoxic T lymphocytes (CTLs), and memory T cells to the lungs of BCG-immunized mice. These findings were observed together with a transcriptional shift towards antigen presentation and tissue repair [56].…”
Section: The Bcg Nses Against Intracellular Pathogens Comprise Ti And...mentioning
confidence: 82%
See 1 more Smart Citation
“…Single-cell transcriptome profiling demonstrated higher recruitment of plasma cells, Th1, Th17, regulatory T cells (Treg), cytotoxic T lymphocytes (CTLs), and memory T cells to the lungs of BCG-immunized mice. These findings were observed together with a transcriptional shift towards antigen presentation and tissue repair [56].…”
Section: The Bcg Nses Against Intracellular Pathogens Comprise Ti And...mentioning
confidence: 82%
“…were as susceptible as the unvaccinated group to intranasal (i.n) or intratracheal (i.t) infection with SARS-CoV-2/SB2 (B.4 lineage) [29]. In turn, other studies demonstrated a different outcome [55,56]. Zhang et al, 2022, showed that i.v.…”
Section: The Bcg Nses Against Intracellular Pathogens Comprise Ti And...mentioning
confidence: 99%
“…Given the implications of this study to the nonspecific effects of vaccines via ncRNAs and other heterologous mechanisms it is of interest to note the reported beneficial effects of prior BCG vaccination against COVID-19 infection [2,7,8,112,113]. Both influenzas, diphtheria, and tetanus vaccines have likewise been suggested to reduce serious COVID-19 outcomes [114].…”
Section: Nonspecific Effects Of Vaccinesmentioning
confidence: 97%
“…Given the implications of this study to the non-specific effects of vaccines via ncRNAs and other heterologous mechanisms it is of interest to note the reported beneficial effects of prior BCG vaccination against COVID-19 infection [5,6,117,118]. Both influenzas, diptheria, and tetanus vaccines have likewise been suggested to reduce serious COVID-19 outcomes [119].…”
Section: Non-specific Effects Of Vaccinesmentioning
confidence: 98%